2017
DOI: 10.1177/2050640617732886
|View full text |Cite
|
Sign up to set email alerts
|

Is de novo hepatocellular carcinoma after transjugular intrahepatic portosystemic shunt increased?

Abstract: Background: Portal hypertension is a major complication of liver cirrhosis. Transjugular intrahepatic portosystemic shunt is effective in treatment of portal hypertension. However, decreased parenchymal portal venous flow after transjugular intrahepatic portosystemic shunt insertion favours ischaemic liver injury which has been discussed to induce hepatocarcinogenesis causing hepatocellular cancer. Aim: This study aimed to explore the association between transjugular intrahepatic portosystemic shunt placement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…TIPS were not associated with an increase in the summed diameter of lesions on explant minus the summed diameter of lesions on imaging when comparing patients with the same number of explant lesions, suggesting that TIPS impact the identification of lesions more than they underestimate the size of identified lesions. Prior studies have not demonstrated a higher incidence of occult malignancy in patients with TIPS, but diagnoses have been made based on imaging modalities, (22)(23)(24) which we now suggest may be of decreased utility in these patients.…”
Section: Original Article | 1259mentioning
confidence: 78%
See 2 more Smart Citations
“…TIPS were not associated with an increase in the summed diameter of lesions on explant minus the summed diameter of lesions on imaging when comparing patients with the same number of explant lesions, suggesting that TIPS impact the identification of lesions more than they underestimate the size of identified lesions. Prior studies have not demonstrated a higher incidence of occult malignancy in patients with TIPS, but diagnoses have been made based on imaging modalities, (22)(23)(24) which we now suggest may be of decreased utility in these patients.…”
Section: Original Article | 1259mentioning
confidence: 78%
“…They also did not differ in terms of the incidence of PVT, extent of PVT into the splenic and/or mesenteric veins, presence of occlusive PVT, or thrombotic involvement of both the portal trunk and its branches (Table 1). A significant difference between subgroups included a higher biochemical MELD score in patients with TIPS (17 [IQR, [15][16][17][18][19][20][21][22] versus 12 [IQR, [9][10][11][12][13][14][15][16][17][18]; P < 0.001). Allocation MELD scores were not dissimilar between groups (24 [IQR, [21][22][23][24][25][26][27][28] versus 25 [IQR, [22][23][24][25][26][27][28][29]), as fewer exception points were granted to the TIPS group given their less frequent identification of pretransplant HCC.…”
Section: Original Article | 1251mentioning
confidence: 99%
See 1 more Smart Citation
“…Several subsequent studies did not detect an association between TIPS and HCC. [60][61][62][63] To date, there is no convincing evidence that the presence of TIPS by itself increases the risk for developing HCC or results in delay in its diagnosis.…”
Section: Hepatocellular Carcinoma Hcc In the Setting Of Tipsmentioning
confidence: 99%
“…The positive correlation between (the degree of) PH, carcinogenesis and thus HCC development was pointed out in different publications. Conversely, reduction of portal pressure by insertion of transjugular intrahepatic portosystemic shunt (TIPS) is significantly associated with reduced rates of de novo HCC (6). The results of Marasco and colleagues are therefore not exceedingly surprising: severity of liver fibrosis or cirrhosis, mirrored by spleen stiffness as indicator of PH, is closely related to HCC development.…”
mentioning
confidence: 99%